Exploring the Moderating Effect of Interpersonal Emotion Regulation Between the Integration of Opportunity and Resource and Entrepreneurial Performance - Li, Na; Sun, Yu; Jiang, Dake; Yang, Xiu (Frontiers in Psychology, 2021)
This study explains how start-ups obtain a high accumulated performance by aligning and employing an integration between opportunity and resource (IOR) in a dynamic environment, and whether these potential benefits are associated with interpersonal emotion regulation. Using 274 enterprise samples, the findings confirm that IOR has a significant positive effect on entrepreneurial performance. In addition, positive emotion regulation and interpersonal relationship regulation positively moderate the relationship between IOR and entrepreneurial performance. The paper proposes a new concept of IOR and measured it for the first time. Then, the relationship between IOR, interpersonal emotion regulation and entrepreneurial performance has been explored. This research not only systematically integrates opportunities and resources, avoids the separation between them, but also helps to reveal the context of entrepreneurship research, enrich entrepreneurship theory and expand the boundaries.